Positive electrode and lithium secondary battery including same

The double-layer active material configuration in lithium iron phosphate-based positive electrodes addresses the challenges of reduced adhesion and conductivity, resulting in improved energy density and battery capacity.

JP2025507715AActive Publication Date: 2025-03-21LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024550612
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-02
Filing Date
2023-11-29
Publication Date
2025-03-21
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

Lithium iron phosphate-based positive electrodes in lithium secondary batteries face challenges with reduced lithium mobility and low electrical conductivity, leading to particle aggregation, decreased adhesion strength, and reduced battery capacity.

Method used

A positive electrode structure with a double-layer active material configuration, where the first active material layer has a higher content of linear conductive material and rubber-based binder compared to the second active material layer, improving adhesion and electrical conductivity.

Benefits of technology

The enhanced adhesion strength and electrical conductivity of the positive electrode lead to improved energy density, reduced particle aggregation, and increased battery capacity, while preventing detachment during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507715000001
    Figure 2025507715000001
  • Figure 2025507715000002
    Figure 2025507715000002
  • Figure 2025507715000003
    Figure 2025507715000003
Patent Text Reader

Abstract

The present invention relates to a positive electrode and a lithium secondary battery manufactured using the same, which includes a first active material layer and a second active material layer sequentially stacked on a positive electrode current collector, in which the conductive material contained in the first active material layer is a linear conductive material, and the content of the linear conductive material contained in the first active material layer is higher than that in the second active material layer, thereby having the effect of increasing the adhesive strength between the positive electrode current collector and the positive electrode active material layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0166976 dated December 2, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a positive electrode and a lithium secondary battery including the same. [Background technology]

[0003] As technological development and demand for electric vehicles and energy storage systems (ESS) increases, the demand for batteries as energy sources is rapidly increasing, and research into batteries that can meet various requirements is being conducted in a wide range of areas. In particular, research into lithium secondary batteries, which have high energy density as a power source for such devices and have excellent life and cycle characteristics, is being actively conducted.

[0004] Typically, in terms of battery shape, there is a high demand for square-type secondary batteries and pouch-type secondary batteries that are thin and can be applied to products such as mobile phones, and in terms of materials, there is a high demand for lithium secondary batteries such as lithium ion batteries and lithium ion polymer batteries that have advantages such as high energy density, discharge voltage, and output stability.

[0005] In general, such a secondary battery has an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between them, built into a battery case, and has a structure in which positive and negative electrode tabs are welded to two electrode tabs and sealed so as to be exposed to the outside of the battery case. These electrode tabs are in contact with and electrically connected to an external device, and the secondary battery supplies power to the external device or is supplied with power from the external device through the electrode tabs.

[0006] Lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (LNCMO), lithium iron phosphate (LFP), etc. are used as positive electrode active materials for lithium secondary batteries.

[0007] Lithium iron phosphate is low-cost because it contains iron, which is an abundant and low-cost material. In addition, the toxicity of lithium iron phosphate is low, so using lithium iron phosphate can reduce environmental pollution. In addition, because lithium iron phosphate has an olivine structure, the active material structure can be stably maintained at high temperatures compared to lithium transition metal oxides with a layered structure. This has the advantage of providing excellent high-temperature stability and high-temperature life characteristics for the battery.

[0008] However, lithium iron phosphate has a problem of lower lithium mobility and low electrical conductivity compared to lithium transition metal oxides such as lithium nickel cobalt manganese oxide. Therefore, in the past, lithium iron phosphate with a small average particle size was used to form a short lithium migration path, and the surface of the lithium iron phosphate was coated with carbon to improve electrical conductivity, and an excessive amount of conductive material was used.

[0009] However, as the size of lithium iron phosphate particles decreases, the specific surface area increases, and lithium iron phosphate with a carbon-coated surface has reduced wettability with a solvent. As a result, lithium iron phosphate particles are severely aggregated, the stability and coating processability of the positive electrode slurry are reduced, and the lithium iron phosphate and the binder are not effectively mixed, resulting in a decrease in the adhesive strength between the positive electrode current collector and the positive electrode active material layer in the manufactured positive electrode (hereinafter, positive electrode adhesive strength). This phenomenon can be exacerbated in high-loading positive electrodes.

[0010] If the adhesive strength of the positive electrode is reduced, the positive electrode active material layer may be detached during the manufacture of the electrode or during charging and discharging, which may lead to an increase in battery resistance and a decrease in the capacity of the secondary battery.

[0011] As the demand for high energy density secondary batteries increases, the lithium iron phosphate-containing cathode is expected to achieve a 550 mg / 25 cm 2 There is a demand for a technology that can improve the adhesion of the positive electrode while ensuring the above loading amount. Summary of the Invention [Problem to be solved by the invention]

[0012] The present invention is made to solve the above-mentioned problems, and aims to provide a positive electrode having excellent positive electrode adhesion by making the content ratios of the conductive material in the first active material layer and the second active material layer different in order to increase the adhesive strength of the positive electrode, and a lithium secondary battery manufactured using the same. [Means for solving the problem]

[0013] The present invention provides a positive electrode. In one embodiment, the positive electrode according to the present invention includes a positive electrode current collector, a first active material layer formed on one or both sides of the positive electrode current collector, and a second active material layer formed on the first active material layer, the first active material layer and the second active material layer each including a positive electrode active material, a linear conductive material, a rubber-based binder, a fluorine-based binder, and a rubber-based dispersant, the rubber-based binder included in the first active material layer and the second active material layer is a hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 to 500 kg / mol, the rubber-based dispersant included in the first active material layer and the second active material layer is a hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10 to 50 kg / mol, and the content of the linear conductive material included in the first active material layer is greater than the content of the conductive material included in the second active material layer.

[0014] In a specific example, the linear conductive material contained in each of the first and second active material layers according to the present invention satisfies the following condition 1.

[0015] [Condition 1] 0.5≦E2 / E1≦0.9

[0016] E1 represents the content (wt%) of the linear conductive material contained in the first active material layer, E2 represents the content (wt %) of the linear conductive material contained in the second active material layer.

[0017] In another specific example, the linear conductive material of the present invention is contained in the first active material layer in the range of 1.0 wt % to 1.5 wt % and in the second active material layer in the range of 0.4 wt % to 0.95 wt %.

[0018] In another specific example, the fluorine-based binder contained in each of the first and second active material layers of the present invention satisfies the following condition 2.

[0019] [Condition 2] 0.5≦P2 / P1≦0.8

[0020] P1 represents the content (wt%) of the fluorine-based binder contained in the first active material layer, P2 represents the content (wt %) of the fluorine-based binder contained in the second active material layer.

[0021] In another specific example, the fluorine-based binder of the present invention is contained in the first active material layer in the range of 2.0 wt % to 2.5 wt %, and in the second active material layer in the range of 1.2 wt % to 1.8 wt %.

[0022] In another specific example, the rubber-based binder contained in the first active material layer and the second active material layer satisfies the following condition 3.

[0023] [Condition 3] 1.0≦R2 / R1≦1.4

[0024] R1 represents the content (wt%) of the rubber-based binder contained in the first active material layer, R2 represents the content (wt %) of the rubber binder contained in the second active material layer.

[0025] In another specific example, the rubber-based binder is contained in the first active material layer in a range of 0.3 wt % to 0.7 wt %, and in the second active material layer in a range of 0.4 wt % to 0.8 wt %.

[0026] In another specific example, the total content (wt %) of the fluorine-based binder and the rubber-based binder contained in the first active material layer and the second active material layer is in the range of 1.5 or more.

[0027] In another embodiment, the porosity of the positive electrode is in the range of 26% to 34% (v / v).

[0028] In another example, in a vacuum-dried positive electrode, the adhesive strength measured during an adhesive strength evaluation in which a positive electrode active material layer including a first active material layer and a second active material layer is peeled off at 90° from a positive electrode current collector is 45 gf / 20 mm or more.

[0029] In a specific example, the positive electrode active material includes lithium iron phosphate, and the lithium iron phosphate is a compound represented by the following Chemical Formula 1.

[0030] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b

[0031] In the above Chemical Formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.

[0032] In another specific example, the linear conductive material is a carbon nanotube.

[0033] The present invention also provides a lithium secondary battery produced using the above-mentioned positive electrode. Effect of the Invention

[0034] In the positive electrode according to the present invention, the content of the linear conductive material contained in the first active material layer and the second active material layer may be made different, and as the positive electrode adhesive strength is improved, the content of the binder may be reduced and the content of the positive electrode active material may be increased, thereby improving the energy density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Since the present invention can be modified in various ways and can have various forms, specific embodiments are illustrated in the drawings and described in detail in the text, but this is not intended to limit the present invention to the specific disclosed forms, and it can be understood as including all modifications, equivalents, or alternatives within the spirit and technical scope of the present invention.

[0036] In this application, the terms "comprise" and "have" are intended to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and may be understood as not precluding the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof. In addition, when a layer, film, region, plate, or other part is described as being "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part in between. Conversely, when a layer, film, region, plate, or other part is described as being "under" another part, this includes not only the case where it is "directly under" the other part, but also the case where there is another part in between. In addition, in this application, being "on" may include not only the case where it is located on the top, but also the case where it is located on the bottom.

[0037] In this specification, D 50 D means the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50can be measured, for example, by using a laser diffraction method. The laser diffraction method generally enables measurement of particle sizes from the submicron range to several mm, and can provide results with high reproducibility and high resolution.

[0038] In this specification, the "specific surface area" is measured by the BET method, and specifically, it can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan.

[0039] In this specification, the term "weight average molecular weight (Mw)" refers to a value converted to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value converted from a value measured under the following conditions using GPC, and standard polystyrene from an Agilent system was used to create a calibration curve.

[0040] <Measurement conditions> Measuring instrument: Agilent GPC (Agulent 1200 series, USA) Column: PL Mixed B 2 pieces connected Column temperature: 40℃ Eluent: Tetrahydrofuran Flow rate: 1.0ml / min Concentration: ~1mg / ml (100μl injection)

[0041] The positive electrode adhesive strength in this specification can be measured by the following method. A positive electrode cut to a length of 150 mm and a width of 20 mm is prepared, and the positive electrode active material layer is made to face a slide glass of a length of 75 mm and a width of 25 mm, and the positive electrode is attached to the slide glass in the longitudinal direction using double-sided tape. That is, the slide glass is attached to an area corresponding to half of the longitudinal direction of the positive electrode. Then, a roller is rolled 10 times so that the double-sided tape is evenly attached to prepare an evaluation sample. Next, the slide glass part of the evaluation sample is fixed to the sample stage of a Universal Testing Machine (UTM) (LS5, AMETEK), and the half of the positive electrode to which the slide glass is not attached is connected to the load cell of the UTM device. A force of 90° is applied to the load cell at a speed of 100 mm / min, and the load applied to the load cell is measured while moving it to 50 mm. At this time, the average value of the load measured in the 20 mm to 40 mm section of the running section is calculated. This is repeated a total of five times, and the average value is evaluated as the positive electrode adhesive strength (gf / 20 mm) of each sample.

[0042] The present invention provides a positive electrode and a lithium secondary battery produced using the same.

[0043] Lithium iron phosphate, which is generally used as a positive electrode active material, has a lower lithium mobility and lower electrical conductivity than lithium transition metal oxides such as lithium nickel cobalt manganese oxide, so lithium iron phosphate with a small average particle size is mainly used as a positive electrode active material. However, when the size of the lithium iron phosphate particles is small, the specific surface area increases, which causes severe particle aggregation and the lithium iron phosphate and binder are not effectively mixed, resulting in a decrease in the positive electrode adhesive strength. As a result, there is a problem in that the positive electrode active material layer is detached during electrode manufacturing or charging and discharging, increasing the battery resistance and decreasing the capacity of the secondary battery.

[0044] Therefore, the present invention is a positive electrode in which a first active material layer is formed on a positive electrode current collector and a second active material layer is formed on the first active material layer, the rubber binder contained in each of the first active material layer and the second active material layer is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 to 500 kg / mol, the rubber dispersant is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10 to 50 kg / mol, and the content of the linear conductive material contained in the first active material layer is greater than the content of the conductive material contained in the second active material layer. In this case, the dispersibility of the lithium iron phosphate particles is improved to suppress their aggregation, the migration of the binder is suppressed, and the adhesive strength of the positive electrode is greatly improved.

[0045] Hereinafter, the positive electrode according to the present invention and the lithium secondary battery produced using the same will be described in detail.

[0046] <Positive electrode>

[0047] A positive electrode according to one embodiment of the present invention includes a positive electrode current collector, a first active material layer formed on one or both sides of the positive electrode current collector, and a second active material layer formed on the first active material layer, the first active material layer and the second active material layer each including a positive electrode active material, a linear conductive material, a rubber-based binder, a fluorine-based binder, and a rubber-based dispersant, the rubber-based binder included in each of the first active material layer and the second active material layer is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 kg / mol to 500 kg / mol, the rubber-based dispersant included in each of the first active material layer and the second active material layer is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10 kg / mol to 50 kg / mol, and the content of the linear conductive material included in the first active material layer is greater than the content of the conductive material included in the second active material layer.

[0048] The positive electrode according to one embodiment of the present invention has a structure in which the positive electrode active material layer is in direct contact with the positive electrode current collector due to excellent interfacial adhesion between the positive electrode current collector and the positive electrode active material layer (including both the first active material layer and the second active material layer), and does not need to include a separate layer for improving adhesion between the positive electrode active material layer and the positive electrode current collector. That is, the positive electrode according to one embodiment of the present invention can exhibit excellent interfacial adhesion even without including a separate layer such as a binding layer, adhesive layer, bonding layer, or primer coating layer that may be interposed between the positive electrode current collector and the positive electrode active material layer for improving adhesion.

[0049] A positive electrode according to one embodiment of the present invention includes a positive electrode active material layer composed of a first active material layer and a second active material layer. Specifically, the positive electrode according to the present invention includes a positive electrode current collector, a first active material layer formed on one or both sides of the positive electrode current collector, and a second active material layer formed on the first active material layer.

[0050] When the positive electrode active material layer is formed as a single layer, during the drying process after applying the positive electrode slurry to the positive electrode current collector, a part of the binder adjacent to the current collector may move toward the electrode surface as the solvent evaporates. As a result, the binder content at the part where the positive electrode active material layer contacts the positive electrode current collector after drying is reduced compared to before drying, and the adhesive strength of the finally obtained positive electrode (adhesive strength between the positive electrode active material layer and the positive electrode current collector) may also be reduced.

[0051] In a battery using a positive electrode with such low adhesive strength, detachment of the positive electrode current collector and the positive electrode active material layer may occur during charging and discharging, and a swelling phenomenon in which the thickness of the positive electrode and the battery including the same gradually increases may occur, and electrochemical characteristics such as the capacity and efficiency of the battery may gradually decrease.

[0052] Therefore, the present invention is designed to solve the problems that arise in a positive electrode having a single layer structure, and forms a positive electrode active material layer structure into a double layer structure, and the binder content of the active material slurry for forming the lower layer (first active material layer) is higher than that of the active material slurry for forming the upper layer (second active material layer).

[0053] Specifically, the first active material layer and the second active material layer each independently contain a positive electrode active material, a binder, a conductive material, and a dispersant, and the content of the binder contained in the first active material layer is designed to be higher than the content of the binder contained in the second active material layer.

[0054] On the other hand, the positive electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, the positive electrode current collector may be made of stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like.

[0055] The positive electrode current collector may have a thickness of 3 μm to 500 μm, and may have fine irregularities on its surface to enhance adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0056] The first active material layer and the second active material layer may each contain a positive electrode active material, a linear conductive material, a rubber-based binder, a fluorine-based binder, and a rubber-based dispersant.

[0057] Hereinafter, each component contained in the positive electrode active material layer will be specifically described.

[0058] (1) Positive electrode active material

[0059] The present invention includes lithium iron phosphate as a positive electrode active material. Since lithium iron phosphate has an olivine structure, the active material structure is more stable at high temperatures than lithium transition metal oxides having a layered structure. As a result, when lithium iron phosphate is used as a positive electrode active material, the high temperature stability and high temperature life characteristics of the positive electrode are significantly improved, thereby reducing the risk of fire in a lithium secondary battery including the positive electrode.

[0060] The lithium iron phosphate may be a compound represented by the following formula 1:

[0061] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b

[0062] In the above Chemical Formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.

[0063] For example, the lithium iron phosphate can be LiFePO4.

[0064] In the present invention, the term "monolith structure" refers to a structure in which particles are not aggregated with each other in terms of morphology and exist in independent phases. A particle structure that is contrasted with such a monolith structure is a structure in which small particles ("primary particles") are physically and / or chemically aggregated to form relatively large particles ("secondary particles").

[0065] When lithium iron phosphate has a monolithic structure made of primary particles, the possibility of the lithium iron phosphate particles cracking during rolling is small compared to when it is made of secondary particles, which is preferable because capacity loss due to detachment of the cracked particles is small. Also, when lithium iron phosphate is made of monolithic primary particles, it can be said to be preferable in terms of interfacial adhesion between the positive electrode current collector and the positive electrode active material layer because it can mitigate the migration of the binder during the drying process of the positive electrode slurry.

[0066] The lithium iron phosphate may include a carbon coating layer on the surface. When a carbon coating layer is formed on the surface of the lithium iron phosphate, the electrical conductivity is improved, and the resistance characteristics of the positive electrode may be improved.

[0067] The carbon coating layer may be formed using at least one raw material selected from the group consisting of glucose, sucrose, lactose, starch, oligosaccharides, polyoligosaccharides, fructose, cellulose, furfuryl alcohol polymers, ethylene and ethylene oxide block copolymers, vinyl resins, cellulose resins, phenol resins, pitch resins, and tar resins. Specifically, the carbon coating layer may be formed through a process of mixing the raw material with the lithium iron phosphate and then heat treating the mixture.

[0068] Average particle size of lithium iron phosphate D 50 The average particle diameter D of the positive electrode active material may be 0.8 μm to 20.0 μm, specifically 0.9 μm to 10.0 μm, and more specifically 0.9 μm to 3.0 μm. 50 When satisfies the above range, the mobility of lithium in the lithium iron phosphate is improved, and the charge / discharge characteristics of the battery can be improved.

[0069] The BET specific surface area of ​​lithium iron phosphate is 5m 2 / g~20m 2 / g, specifically 7m 2 / g~18m 2 / g, more specifically 9m 2 / g~16m 2 / g. This range corresponds to a lower value compared to typical lithium iron phosphate. When this range is satisfied, aggregation of the lithium iron phosphate can be effectively suppressed even in a positive electrode slurry composition having a relatively low content of a dispersant.

[0070] The lithium iron phosphate of the present invention is characterized in that it is contained in different contents in the first active material layer and the second active material layer. In a specific example, the lithium iron phosphate may be contained in a range of 95.0 wt% to 96.3 wt% based on the total solid content of the positive electrode slurry composition constituting the first active material layer. Also, it may be contained in a range of 96.5 wt% to 97.5 wt% based on the total solid content of the positive electrode slurry composition constituting the second active material layer. Preferably, it may be contained in a range of 95.5 wt% to 96.0 wt% based on the total solid content of the positive electrode slurry composition constituting the first active material layer, and may be contained in a range of 96.7 wt% to 97.0 wt% based on the total solid content of the positive electrode slurry composition constituting the second active material layer. When the content of the lithium iron phosphate satisfies the above range, sufficient positive electrode energy density can be ensured, thereby improving the battery capacity of the positive electrode.

[0071] (2) Conductive material

[0072] The conductive material of the present invention is a linear conductive material. Here, the term "linear (needle type)" means a needle-like particle shape, for example, an aspect ratio (length / diameter value) in the range of 50 to 650, specifically 60 to 300, or 100 to 300.

[0073] The linear conductive material has higher electrical conductivity than the dotted conductive material, and is distributed between the active materials in the active material layer in a form that wraps the active material surface, which is advantageous for forming a conductive network and can reduce the amount of the conductive material. In addition, the linear conductive material does not block the pores, which are the empty spaces between the active materials, which is advantageous for the development of the pores, and has the effect of reducing the diffusion resistance by facilitating the diffusion of lithium ions.

[0074] The linear conductive material may be carbon nanotubes (CNT), vapor-grown carbon fibers (VGCF), carbon nanofibers (CNF), or a mixture of two or more of these, and is preferably carbon nanotubes. The conductive network of carbon nanotubes can reduce the lifting of the binder during the drying process of the positive electrode slurry, and is therefore preferable as the conductive material contained in the positive electrode of the present invention.

[0075] The present invention is characterized in that the content of the linear conductive material contained in the first active material layer is greater than the content of the conductive material contained in the second active material layer.

[0076] When the positive electrode active material layer is formed as a single layer as described above, during the drying process after the application of the positive electrode slurry, a part of the binder adjacent to the positive electrode current collector may move toward the electrode surface as the solvent evaporates. As a result, the binder content in the part in contact with the current collector after drying may decrease compared to before drying after application of the active material slurry, and the adhesive strength of the finally obtained positive electrode may also decrease.

[0077] In a battery using a positive electrode with such low adhesive strength, detachment of the positive electrode current collector and the positive electrode active material layer may occur during charging and discharging, and a swelling phenomenon in which the thickness of the positive electrode and the battery including the same gradually increases may occur, and electrochemical characteristics such as the capacity and efficiency of the battery may gradually decrease.

[0078] In order to solve the problems that occur in a positive electrode having a single layer structure, the positive electrode of the present invention is configured such that the positive electrode active material layer is formed into a double layer structure, and the positive electrode slurry forming the first active material layer, which is the lower layer, has a higher linear conductive material content than the positive electrode slurry forming the second active material layer, which is the upper layer. In this case, the adhesive strength between the positive electrode current collector and the positive electrode active material layer (including the first active material layer and the second active material layer) is increased compared to when the positive electrode slurry forming the second active material layer, which is the upper layer, has a higher linear conductive material content than the positive electrode slurry forming the first active material layer, which is the lower layer. This is because the migration of the binder due to the conductive network structure of the linear conductive material, especially the carbon nanofiber, during the electrode drying process is mitigated.

[0079] In addition, a comparison of thickness changes occurring during charging and discharging between a positive electrode having a higher linear conductive material content in the positive electrode slurry forming the first active material layer (lower layer) than in the positive electrode slurry forming the second active material layer (upper layer) and a positive electrode having a higher linear conductive material content in the positive electrode slurry forming the second active material layer (upper layer) than in the positive electrode slurry forming the first active material layer (lower layer) showed that the former had less thickness change, which is due to the relatively higher adhesive strength between the positive electrode current collector and the positive electrode active material layer (including the first active material layer and the second active material layer) than the latter, which can prevent detachment of the electrode and suppress swelling.

[0080] The linear conductive material of the present invention is characterized in that it is contained in the first active material layer and the second active material layer at different contents. In a specific example, the linear conductive material contained in each of the first active material layer and the second active material layer may be configured to satisfy the following condition 1.

[0081] [Condition 1] 0.5≦E2 / E1≦0.9

[0082] E1 represents the content (wt%) of the linear conductive material contained in the first active material layer, E2 represents the content (wt %) of the linear conductive material contained in the second active material layer.

[0083] More specifically, the linear conductive material may be contained in the first active material layer in a range of 1.0 wt% to 1.5 wt% and in the second active material layer in a range of 0.4 wt% to 0.95 wt%, and preferably, the linear conductive material may be contained in the first active material layer in a range of 1.1 wt% to 1.4 wt% and in the second active material layer in a range of 0.6 wt% to 0.90 wt%. When the content of the conductive material in the first active material layer and the second active material layer satisfies the above range, the migration of the binder due to the conductive network structure is mitigated, and the adhesive force between the positive electrode current collector and the positive electrode active material layer (including the first active material layer and the second active material layer) can be increased, and the electrical conductivity of the positive electrode can be improved by ensuring the positive electrode conductive network.

[0084] (3) Binder

[0085] The binder of the present invention includes both fluorine-based binders and rubber-based binders. The fluorine-based binder includes a PVDF-based polymer containing vinylidene fluoride (VDF) as a monomer. Specific examples of the PVDF-based polymer include a PVDF single polymer, PVDF-HFP (Poly(vinylidene fluoride-co-hexafluoropropylene)), PVDF-CTFE (Poly(vinylidene fluoride-co-chlorotrifluoroethylene)), PVDF-TFE (Poly(vinylidene tetrafluoroethylene)), and PVDF-TrFE (Poly(vinylidene trifluoroethylene)).

[0086] The fluorine-based binder, together with the rubber-based binder, imparts adhesive strength between the positive electrode active material and the conductive material, and adhesive strength between the current collector and the positive electrode active material layer.

[0087] The weight average molecular weight (Mw) of the fluorine-based binder according to the present invention is 800 kg / mol to 1,500 kg / mol, preferably 900 kg / mol to 1,400 kg / mol, and more preferably 950 kg / mol to 1,200 kg / mol. If the weight average molecular weight of the fluorine-based binder is less than the above range, the adhesive strength improving effect may be insufficient, whereas if it exceeds the above range, the viscosity of the positive electrode slurry increases at the same solid content, which may reduce the coating stability, which is not preferable.

[0088] The fluorine-based binder may be contained in the first active material layer in a range of 2.0 wt % to 2.5 wt % and in the second active material layer in a range of 1.2 wt % to 1.8 wt %, and preferably in the first active material layer in a range of 2.1 wt % to 2.4 wt %, and in the second active material layer in a range of 1.3 wt % to 1.6 wt %.

[0089] Meanwhile, the rubber-based binder improves the flexibility of the positive electrode, increases the loading amount of the positive electrode, and improves rolling performance. In addition, the improved flexibility of the positive electrode helps maintain the adhesive strength of the positive electrode when it is subjected to a physical impact from outside the positive electrode, thereby contributing to improving the adhesive strength.

[0090] The rubber-based binder of the present invention may be hydrogenated nitrile butadiene rubber (HNBR). The hydrogenated nitrile butadiene rubber (HNBR) is made by hydrogenating nitrile butadiene rubber (NBR) so that the double bonds originally contained in the nitrile butadiene rubber (NBR) are converted to single bonds.

[0091] Specifically, the rubber-based binder contained in each of the first and second active material layers is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 kg / mol to 500 kg / mol. When the weight average molecular weight (Mw) of the hydrogenated nitrile butadiene rubber (HNBR) is within the above range, the adhesive strength and flexibility of the first and second active material layers can be improved, and the rolling density of the positive electrode can be increased. As the rolling density increases, the positive electrode resistance decreases, and the adhesive strength between the positive electrode current collector and the positive electrode active material layer can be increased.

[0092] Meanwhile, the rubber-based binder contained in the first active material layer and the second active material layer may be configured to satisfy the following condition 3.

[0093] [Condition 3] 1.0≦R2 / R1≦1.4

[0094] R1 represents the content (wt%) of the rubber-based binder contained in the first active material layer, R2 represents the content (wt %) of the rubber binder contained in the second active material layer.

[0095] Specifically, the rubber binder may be contained in the first active material layer in a range of 0.3 wt % to 0.7 wt %, and in the second active material layer in a range of 0.4 wt % to 0.8 wt %. Preferably, the rubber binder may be contained in the first active material layer in a range of 0.4 wt % to 0.6 wt %, and in the second active material layer in a range of 0.5 wt % to 0.7 wt %.

[0096] Meanwhile, the total content of the fluorine-based binder and the rubber-based binder may be configured to be greater in the first active material layer than in the second active material layer. Specifically, the positive electrode is characterized in that the positive electrode active material layer has a double-layer structure composed of a first active material layer and a second active material layer, and the binder content of the slurry forming the lower layer, the first active material layer, is higher than that of the upper layer, the second active material layer.

[0097] In addition, in the positive electrode according to an embodiment of the present invention, the total content (wt%) of the fluorine-based binder and the rubber-based binder contained in the first active material layer and the second active material layer may be in the range of 1.5 or more. If the total content of the binder (including the fluorine-based binder and the rubber-based binder) is less than 1.5 wt%, there is a problem in that the adhesive strength between the positive electrode active material layer (including the first active material layer and the second active material layer) and the positive electrode current collector decreases.

[0098] When the positive electrode active material layer is formed as a single layer, some of the binder adjacent to the current collector may migrate toward the electrode surface as the solvent evaporates during drying. As a result, the binder content in the area in contact with the current collector after drying may decrease compared to before drying after coating the positive electrode slurry, and the adhesive strength of the final positive electrode (adhesive strength between the active material layer and the current collector) may also decrease.

[0099] In a battery using such a positive electrode with low adhesive strength, detachment of the positive electrode current collector and the positive electrode active material layer may occur during charging and discharging, and the thickness of the positive electrode and the battery including the same may gradually increase, resulting in a swelling phenomenon, which may gradually decrease the electrochemical characteristics such as the capacity and efficiency of the battery. Therefore, in order to solve the problem of decreased adhesive strength of the positive electrode that occurs in such a single layer structure, the present invention is characterized in that the structure of the positive electrode active material layer is a double layer structure, and the binder content of the first active material layer, which is the lower layer, is higher than that of the second active material layer, which is the upper layer of the positive electrode active material layer.

[0100] More specifically, the total content of the binders (including fluorine-based binders and rubber-based binders) contained in the first active material layer may be in the range of 1.0 to 1.7 times the total content of the binders contained in the second active material layer, and preferably in the range of 1.2 to 1.5 times. When the total content ratio of the binders is in the above range, even if a part of the binder in the first active material layer, which is the lower layer, moves toward the electrode surface during the drying process, an excessive amount of binder remains in the first active material layer of the positive electrode finally obtained after drying compared to a positive electrode having a single layer structure, so that the decrease in adhesive strength of the positive electrode that occurs during the drying process can be prevented. Therefore, a secondary battery using a positive electrode with improved adhesiveness can suppress detachment of the positive electrode current collector and the positive electrode active material layer during the charging and discharging process, swelling of the positive electrode and the battery including the same, and further the phenomenon of the decrease in electrochemical characteristics during the charging and discharging process of the battery.

[0101] (4) Dispersants

[0102] The first and second active material layers of the present invention also contain a dispersant. The dispersant is used to increase the dispersibility of the components of the active material layer, particularly the dispersibility of the conductive material in the active material. Meanwhile, the dispersant can also act as a thickener.

[0103] The dispersant of the present invention may be hydrogenated nitrile butadiene rubber (HNBR). As described above, hydrogenated nitrile butadiene rubber (HNBR) can improve the adhesive strength and flexibility of the first active material layer and the second active material layer, increase the rolling density, and reduce the positive electrode resistance, and has the effect of increasing the adhesive strength between the positive electrode current collector and the positive electrode active material layer (including the first active material layer and the second active material layer).

[0104] The dispersant may be contained in the first active material layer in a range of 0.2 wt % to 0.5 wt % and in the second active material layer in a range of 0.1 wt % to 0.4 wt %, and preferably in the first active material layer in a range of 0.3 wt % to 0.4 wt %, and in the second active material layer in a range of 0.2 wt % to 0.3 wt %. The binder (including the fluorine-based binder and the rubber-based binder) contained in the first active material layer is greater than the binder (including the fluorine-based binder and the rubber-based binder) contained in the second active material layer, so that a higher content of binder is added to the first active material layer than to the second active material layer in consideration of this.

[0105] On the other hand, the hydrogenated nitrile butadiene rubber (HNBR) constituting the dispersant has the same chemical structure as the hydrogenated nitrile butadiene rubber (HNBR) constituting the binder, but has a different weight average molecular weight (Mw).

[0106] In a specific example, the rubber-based binder contained in each of the first and second active material layers may be hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 kg / mol to 500 kg / mol, and the rubber-based dispersant contained in each of the first and second active material layers may be hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10 kg / mol to 50 kg / mol. The smaller the weight average molecular weight (Mw) of the hydrogenated nitrile butadiene rubber (HNBR) is, the smaller the particle size may be. By configuring the weight average molecular weight (Mw) of the hydrogenated nitrile butadiene rubber (HNBR) used as the conductive material to be smaller than the weight average molecular weight (Mw) of the hydrogenated nitrile butadiene rubber (HNBR) used as the dispersant, the dispersibility of the fluorine-based and rubber-based binders may be improved. In addition, even if the particle size of the lithium iron phosphate-based positive electrode active material is reduced, the agglomeration between the positive electrode active material particles can be prevented, thereby solving the dispersibility problem.

[0107] According to one embodiment of the present invention, the positive electrode may have excellent positive electrode adhesion and flexibility. Specifically, in the positive electrode, the positive electrode active material layer may have improved adhesion to the positive electrode current collector. As a result, a high loading positive electrode may be manufactured, and the cell resistance of the secondary battery may be reduced by preventing the positive electrode from being detached, thereby improving the capacity and output characteristics of the battery, and reducing defects occurring during the manufacturing process.

[0108] Meanwhile, according to one embodiment of the present invention, the positive electrode may have a porosity in the range of 26% to 34% (v / v). Since a positive electrode active material such as lithium iron phosphate having a porosity in the above range can freely move between the electrodes, the cell resistance of the secondary battery may be reduced and the capacity and output characteristics of the battery may be improved.

[0109] Furthermore, according to one embodiment of the present invention, in a vacuum-dried positive electrode, the adhesive strength measured in an adhesive strength evaluation in which the first active material layer and the second active material layer are peeled off at 90° from the positive electrode current collector is 45 gf / 20 mm or more, specifically 50 gf / 20 mm or more, or in the range of 45 to 60 gf / 20 mm.

[0110] <Lithium secondary battery>

[0111] Next, the lithium secondary battery according to the present invention will be described.

[0112] A lithium secondary battery according to an embodiment of the present invention may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0113] In the lithium secondary battery, the positive electrode is as described above. For example, a positive electrode according to one embodiment of the present invention includes a positive electrode current collector, a first active material layer formed on one or both sides of the positive electrode current collector, and a second active material layer formed on the first active material layer, the first active material layer and the second active material layer each including a positive electrode active material, a linear conductive material, a rubber-based binder, a fluorine-based binder, and a rubber-based dispersant, the rubber-based binder included in each of the first active material layer and the second active material layer is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 kg / mol to 500 kg / mol, the rubber-based dispersant included in each of the first active material layer and the second active material layer is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10 kg / mol to 50 kg / mol, and the content of the linear conductive material included in the first active material layer is greater than the content of the conductive material included in the second active material layer.

[0114] The negative electrode can be manufactured, for example, by preparing a composition for forming a negative electrode, which contains a negative electrode active material, a negative electrode binder, and a negative electrode conductive material, on a negative electrode current collector, and then coating the composition on the negative electrode current collector.

[0115] The negative electrode active material is not particularly limited, and generally, a compound capable of reversible intercalation and deintercalation of lithium can be used.Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, and highly crystalline carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; or a composite containing a metallic compound and a carbonaceous material. In addition, examples of low crystalline carbon include soft carbon and hard carbon, and examples of high crystalline carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. Among these, one type alone or a mixture of two or more types may be used, and a metallic lithium thin film may also be used as the negative electrode active material.

[0116] The negative electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing a chemical change in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The negative electrode conductive material may be generally contained in an amount of 1% by weight to 30% by weight, specifically 1% by weight to 20% by weight, and more specifically 1% by weight to 10% by weight, based on the total weight of the negative electrode active material layer.

[0117] The negative electrode binder plays a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The negative electrode binder may be included in an amount of 1% by weight to 30% by weight, specifically 1% by weight to 20% by weight, more specifically 1% by weight to 10% by weight, based on the total weight of the negative electrode active material layer.

[0118] On the other hand, the negative electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, aluminum-cadmium alloy, etc. may be used.

[0119] The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and may have fine irregularities on its surface to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven fabric, etc.

[0120] Meanwhile, in the lithium secondary battery, the separator can be used without any particular limitation as long as it is one that is generally used as a separator in a lithium secondary battery, and in particular, one that has low resistance to ion migration of the electrolyte and excellent electrolyte humidification ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc. can also be used. In addition, the separator can be a porous thin film having a pore diameter of 0.01 μm to 10 μm and a thickness of 5 μm to 300 μm.

[0121] Meanwhile, in the lithium secondary battery, the electrolyte may include an organic solvent and a lithium salt that are generally used in electrolytes, and is not particularly limited.

[0122] The organic solvent may be used without any particular limitation, so long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, examples of the organic solvent that can be used include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether and tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; and carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC).

[0123] Among these, carbonate-based solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant, which can improve the charge / discharge performance of the battery, and low-viscosity chain carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) are more preferred.

[0124] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably contained in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.

[0125] In addition to the above electrolyte components, the electrolyte may further contain one or more additives such as pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the battery life characteristics, suppressing the decrease in battery capacity, improving the battery discharge capacity, etc. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0126] The lithium secondary battery of the present invention may be manufactured by forming an electrode assembly by disposing a separator between a positive electrode and a negative electrode, and then inserting the electrode assembly into a cylindrical or prismatic battery case and then injecting an electrolyte into the battery case. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and then inserted into a battery case and sealed.

[0127] In the case of manufacturing the lithium secondary battery of the present invention, the electrode assembly may be dried to remove at least one organic solvent selected from the group consisting of N-methyl-2-pyrrolidone (NMP), acetone, ethanol, propylene carbonate, ethyl methyl carbonate, ethylene carbonate, and dimethyl carbonate, which was used in manufacturing the positive electrode. If an electrolyte having the same composition as the organic solvent used in manufacturing the positive electrode is used as the electrolyte, the process of drying the electrode assembly may be omitted.

[0128] Unlike the above-described lithium secondary batteries, the lithium secondary battery according to another embodiment of the present invention may be an all-solid-state battery.

[0129] The battery case may be one commonly used in the art, and the shape of the battery case is not limited depending on the application of the battery. For example, the battery case may be a cylindrical type using a can, a square type, a pouch type, a coin type, or the like.

[0130] The lithium secondary battery according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, energy storage systems (ESS), and electric vehicles such as hybrid electric vehicles (HEV), etc.

[0131] The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples alone.

[0132] <Example 1: Production of positive electrode>

[0133] (1) Preparation of cathode slurry

[0134] A positive electrode active material was lithium iron phosphate (S20), a conductive material was carbon nanotubes (CNT), a fluorine-based binder (Kynar (registered trademark), HSV900), a rubber-based binder was hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) of 200 kg / mol, and a dispersant was hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) of 20 kg / mol. The mixture was then mixed at 2500 rpm for 90 minutes using Homo-disperse to prepare a first positive electrode slurry and a second positive electrode slurry.

[0135] Within the first positive electrode slurry, the lithium iron phosphate, conductive material, dispersant, fluorine-based binder, and rubber-based binder were present in a weight ratio of 95.74:1.2:0.36:2.2:0.5.

[0136] Additionally, in the second positive electrode slurry, the lithium iron phosphate, the conductive material, the dispersant, the fluorine-based binder, and the rubber-based binder were present in a weight ratio of 96.96:0.8:0.24:1.4:0.6.

[0137] (2) Manufacturing of positive electrodes

[0138] The first positive electrode slurry was applied to a 20 μm-thick aluminum thin film, and then hot-air dried at 130° C. for 5 minutes so that the solid content of the positive electrode slurry was 99.0% by weight or more. The positive electrode slurry was then rolled by a roll pressing method to form a first active material layer.

[0139] Then, the second positive electrode slurry was coated on the first active material layer, dried with hot air at 130°C for 5 minutes, and then rolled using a roll pressing method to form the first active material layer, thereby preparing a positive electrode having a double layer. At this time, the total loading amount of the positive electrode was 584 mg / 25 cm. 2 and the porosity was 29% (v / v).

[0140] <Examples 2 to 3 and Comparative Examples 1 to 3: Production of Positive Electrodes>

[0141] Positive electrodes were prepared in the same manner as in Example 1, except that the weight ratios of the lithium iron phosphate, the conductive material, the dispersant, the fluorine-based binder, and the rubber-based binder in the first positive electrode slurry and the second positive electrode slurry were changed as shown in Table 1.

[0142] <Examples 4 to 6 and Comparative Examples 4 to 7: Production of Positive Electrodes>

[0143] Positive electrodes were prepared in the same manner as in Example 1, except that the weight average molecular weights of the rubber binder and dispersant in the first and second positive electrode slurries were changed as shown in Table 1.

[0144] <Experimental Example 1: Viscosity measurement of positive electrode slurry>

[0145] The viscosity of each of the positive electrode slurries produced in Examples 1 to 6 and Comparative Examples 1 to 7 was measured, and the results are shown in Table 2.

[0146] Specifically, the positive electrode slurries prepared in Examples 1 to 6 and Comparative Examples 1 to 7 were cooled for 1 hour at room temperature and a relative humidity of 1%, and then the viscosities of the positive electrode slurry compositions were measured at 25° C. and a shear rate of 2.5 / s using a Brookfield viscometer. The viscosity measurements were performed within 2 hours, including the cooling time, after the preparation of the positive electrode slurry compositions.

[0147] <Experimental Example 2: Positive electrode adhesion test>

[0148] The positive electrodes produced in Examples 1 to 6 and Comparative Examples 1 to 7 were each vacuum-dried at 130° C. for 2 hours, and then the adhesive strength between the positive electrode active material layer and the positive electrode current collector was measured. The results are shown in Table 2.

[0149] Specifically, the positive electrodes produced in Examples 1 to 6 and Comparative Examples 1 to 7 were cut to a length of 150 mm and a width of 20 mm, and the positive electrode surface was attached to a slide glass having a length of 75 mm and a width of 25 mm in the longitudinal direction using double-sided tape. That is, the slide glass was attached to an area corresponding to half of the longitudinal direction of the positive electrode. Then, a roller was rotated 10 times to uniformly attach the double-sided tape to produce an evaluation sample.

[0150] Next, the glass slide portion of the evaluation sample was fixed to the sample stage of a Universal Testing Machine (UTM) (product name: LS5, manufacturer: LLOYD), and the positive electrode half to which the glass slide was not attached was connected to the load cell of the UTM device. The load cell was subjected to a 90° force at a speed of 100 mm / min, and the load applied to the load cell was measured while moving it up to 50 mm. At this time, the average value of the load measured in the 20 mm to 40 mm section of the travel section was calculated, and this was repeated five times in total, and the average value was measured as the positive electrode adhesive strength (gf / 20 mm) of each sample.

[0151] [Table 1-1] [Table 1-2]

[0152] [Table 2]

[0153] In the positive electrode of Example 1, the first active material layer contains more conductive material than the second active material layer. On the other hand, in Comparative Examples 1 to 3, the first active material layer contains less conductive material than the second active material layer. It can be confirmed that the positive electrode adhesive strength of Example 1 is superior to the positive electrode adhesive strengths of Comparative Examples 1 to 3. In addition, the positive electrodes of Examples 2 to 3 have different ratios of conductive material contained in the first active material layer and the second active material layer from Example 1, but the conductive material contained in the first active material layer is greater than the conductive material contained in the second active material layer, and it can be confirmed that the positive electrode adhesive strength is superior to that of Comparative Examples 1 to 3, and is smaller than that of Example 1, but does not show a large difference. That is, when the conductive material is contained more in the first active material layer than in the second active material layer as in Examples 1 to 3, the positive electrode adhesive strength is superior to that of Comparative Examples 1 to 3, when the conductive material is contained less in the first active material layer than in the second active material layer.

[0154] Specifically, assuming that E1 represents the content (weight %) of the linear conductive material contained in the first active material layer and E2 represents the content (weight %) of the linear conductive material contained in the second active material layer, Examples 1 to 3 satisfy the following condition 1, but Comparative Examples 1 to 3 do not satisfy the following condition 1.

[0155] [Condition 1] 0.5≦E2 / E1≦0.9

[0156] Therefore, when the positive electrode slurry forming the first active material layer, which is the lower layer, has a higher content of linear conductive material than the positive electrode slurry forming the second active material layer, which is the first active material layer, the adhesive strength between the positive electrode current collector and the positive electrode active material layer (including the first active material layer and the second active material layer) was increased compared to when the positive electrode slurry forming the second active material layer, which is the upper layer, has a higher content of conductive material than the positive electrode slurry forming the first active material layer, which is the lower layer. This is believed to be because the binder migration phenomenon caused by the conductive network structure of the conductive material, particularly the linear conductive material such as carbon nanofiber, was mitigated during the electrode drying process, thereby improving the adhesive strength between the positive electrode current collector and the positive electrode active material layer (including the first active material layer and the second active material layer). A battery using a positive electrode with improved adhesion is expected to be able to improve electrochemical characteristics such as battery capacity and efficiency by preventing detachment of the positive electrode current collector and the positive electrode active material layer during charging and discharging and preventing the swelling phenomenon in which the thickness of the positive electrode and the battery including it gradually increases.

[0157] In the positive electrodes of Example 1 and Examples 4 to 6, the rubber binder contained in each of the first and second active material layers is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 kg / mol to 500 kg / mol, and the rubber dispersant contained in each of the first and second active material layers is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10 kg / mol to 50 kg / mol. On the other hand, Comparative Examples 4 to 7 do not fall within the above range.

[0158] It was shown that the adhesive strength of the positive electrodes of Example 1 and Examples 4 to 6 was far superior to that of the positive electrodes of Comparative Examples 4 to 7. This is because, when the rubber-based binder and the rubber-based dispersant hydrogenated nitrile butadiene rubber (HNBR) contained in the first active material layer and the second active material layer, respectively, have a weight average molecular weight (Mw) within the above range, it is analyzed that the adhesive strength is improved by preventing aggregation between the constituent particles of the positive electrode, improving dispersibility, and preventing the migration of the binder (including the fluorine-based binder and the rubber-based binder) to the electrode surface during the drying process.

[0159] As described above, according to the embodiment of the present invention, the rubber-based binder and the rubber-based dispersant hydrogenated nitrile butadiene rubber (HNBR) contained in the first active material layer and the second active material layer, respectively, have a certain range of weight average molecular weight (Mw), and the content of the linear conductive material contained in the first active material layer is greater than the content of the conductive material contained in the second active material layer, so that the positive electrode can have excellent adhesive strength while containing a large amount of positive electrode active material.

[0160] <Experimental Example 4: Measurement of thickness change of positive electrode>

[0161] The thickness change of each of the positive electrodes prepared in Example 1 and Comparative Example 1 was measured.

[0162] Specifically, the lithium secondary batteries manufactured using the positive electrodes of Example 1 and Comparative Example 1 were charged in CC / CV mode at 25° C. until the SOC reached 30% and 100%, respectively. The lithium secondary batteries of Example 1 and Comparative Example 1 were disassembled, and the thicknesses of the positive electrodes were measured, and the values ​​of the change rates were measured as shown in Table 3 below.

[0163] Meanwhile, the negative electrode of the lithium secondary battery was prepared by adding a mixture of artificial graphite (GT), natural graphite (AGP8) and SiO (KSC6027D) (85:10:5, weight%) as active materials, a mixture of carbon black (Super-C65) and CNT (NCL-H5) as conductive materials, SBR (BM-L302) as binder and CMC (Daicel 2200) as thickener in a ratio of 95.1:1.5:2.3:1.1 to distilled water as solvent to prepare a negative electrode slurry. The negative electrode slurry was coated on one side of a 6μm thick copper foil, and dried and rolled under the same conditions as the positive electrode to prepare the negative electrode.

[0164] The electrolyte was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a 30:70 (volume ratio) organic solvent with additives 0.1% tetravinylsilane (VS2), 1% ethylene sulfate (ESa), 0.5% 1,3-propane sultone (PS), 1% lithium difluorophosphate (DFP), and 0.2% LiBF4, to prepare a non-aqueous electrolyte with 0.7M LiPF6 and 0.5M LiFSI dissolved therein. A separator (DB0905 / BA1,8μm) was placed between the positive and negative electrodes, and the electrolyte was injected to prepare a lithium secondary battery.

[0165] [Table 3]

[0166] It can be seen that, under the same charging state, the positive electrode of Example 1 has less thickness change during charging and discharging compared to the positive electrode of Comparative Example 1. It is analyzed that Example 1 has higher adhesive strength than Comparative Example 1, which can prevent electrode detachment and therefore prevent swelling. Therefore, by configuring the positive electrode so that the content of the linear conductive material contained in the first active material layer is greater than the content of the conductive material contained in the second active material layer, it is possible to improve the adhesive strength of the positive electrode and simultaneously suppress the swelling phenomenon caused by charging and discharging.

[0167] Although the above describes a preferred embodiment of the present invention, a person skilled in the art or having ordinary knowledge in the art can understand that the present invention can be modified and changed in various ways without departing from the spirit and technical scope of the present invention as described in the claims.

[0168] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims.

Claims

1. A positive electrode current collector; a first active material layer formed on one or both surfaces of a positive electrode current collector; a second active material layer formed on the first active material layer, The first active material layer and the second active material layer each contain a positive electrode active material, a linear conductive material, a rubber-based binder, a fluorine-based binder, and a rubber-based dispersant, The rubber-based binder contained in each of the first active material layer and the second active material layer is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 100 kg / mol to 500 kg / mol; The rubber-based dispersant contained in each of the first active material layer and the second active material layer is hydrogenated nitrile butadiene rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10 kg / mol to 50 kg / mol; A positive electrode, wherein the content of the linear conductive material contained in the first active material layer is greater than the content of the conductive material contained in the second active material layer.

2. The positive electrode according to claim 1 , wherein the linear conductive material contained in each of the first active material layer and the second active material layer satisfies the following condition 1: [Condition 1] 0.5≦E2 / E1≦0.9 E1 represents the content (wt%) of the linear conductive material contained in the first active material layer, E2 represents the content (wt %) of the linear conductive material contained in the second active material layer.

3. The linear conductive material is contained in the first active material layer in a range of 1.0 wt % to 1.5 wt %; The positive electrode according to claim 1 , wherein the second active material layer contains the first active material in an amount ranging from 0.4% by weight to 0.95% by weight.

4. The positive electrode according to claim 1 , wherein the fluorine-based binder contained in each of the first active material layer and the second active material layer satisfies the following condition 2: [Condition 2] 0.5≦P2 / P1≦0.8 P1 represents the content (wt%) of the fluorine-based binder contained in the first active material layer, P2 represents the content (wt %) of the fluorine-based binder contained in the second active material layer.

5. The fluorine-based binder is contained in the first active material layer in an amount of 2.0% by weight to 2.5% by weight. The positive electrode according to claim 1 , wherein the second active material layer contains the first active material in an amount ranging from 1.2% by weight to 1.8% by weight.

6. The positive electrode according to claim 1, wherein the rubber-based binder contained in the first active material layer and the second active material layer satisfies the following condition 3: [Condition 3] 1.0≦R2 / R1≦1.4 R1 represents the content (wt%) of the rubber-based binder contained in the first active material layer, R2 represents the content (wt %) of the rubber-based binder contained in the second active material layer.

7. The rubber binder is contained in the first active material layer in an amount of 0.3% by weight to 0.7% by weight. The positive electrode according to claim 1 , wherein the second active material layer contains the first active material in an amount ranging from 0.4% by weight to 0.8% by weight.

8. 2. The positive electrode according to claim 1, wherein the total content (wt %) of the fluorine-based binder and the rubber-based binder contained in the first active material layer and the second active material layer is in the range of 1.5 or more.

9. 10. The positive electrode of claim 1, wherein the porosity is in the range of 26% to 34% (v / v).

10. 2. The positive electrode according to claim 1, wherein an adhesive strength measured in an adhesive strength evaluation in which a positive electrode active material layer including the first active material layer and the second active material layer is peeled off at 90° from a positive electrode current collector in a vacuum-dried positive electrode is 45 gf / 20 mm or more.

11. The positive electrode active material contains lithium iron phosphate, The positive electrode according to claim 1, wherein the lithium iron phosphate is a compound represented by the following chemical formula 1: [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b In the above Chemical Formula 1, M includes one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y; X includes one or more elements selected from the group consisting of F, S, and N; and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.

12. The positive electrode according to claim 1 , wherein the linear conductive material is a carbon nanotube.

13. A lithium secondary battery comprising the positive electrode according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Electrode for battery, battery using it, and its method for manufacturing

    JP2009245925A

  • Nonaqueous electrolyte secondary battery

    JP2015015183A

  • Positive electrode and lithium battery including positive electrode

    JP2020035746A

  • Positive electrode active material pre-dispersion composition, positive electrode for secondary battery, and lithium secondary battery including the same

    JP2020515014A

  • Positive electrode for secondary battery and secondary battery comprising the same

    JP2021007109A